A multi-gateway-based architecture for integrating ad hoc networks with the internet using multiple Foreign Agents. (5th February 2008) - Denko, Mieso K.; Wei, Chen
Mobile Ad hoc Networks (MANETs) are typically considered to be stand-alone autonomous networks that support multi-hop communication without relying on an existing infrastructure. The integration of MANETs and the internet extends network coverage and facilitates hybrid wired and wireless networking. Most earlier approaches, for integrating MANETs with the internet considered fixed gateways and registration by means of a single gateway or Foreign Agent (FA) with unidirectional connectivity. In this paper, we propose an architecture for integrating MANETs and the internet using multiple Mobile Gateways (MGs) and FAs. MGs move within a one-hop or two-hop distance from the FAs. We extended the Ad hoc On Demand Distance Vector (AODV) routing protocol and Mobile IP (MIP) to achieve the integration. The simulation results show that the use of multiple MGs and a hybrid gate discovery mechanism enhances network performance while providing bi-directional internet connectivity in a multiple foreign agent environment.